The Dynamics and Dismantling of White Missionary Privilege - Lewis, Bonnie Sue (Missiology, 2004)
Lest we become too smug that we have moved beyond the ethnocentric attitudes and sins that often marred the work of our missionary forbearers, we are challenged to look again at the policies and practices of the church toward indigenous churches and church leadership. Focusing on the work of the Presbyterian Church (USA) among Native Americans and Native Alaskans, this essay posits that the complex and paradoxical dynamics of white missionary privilege and its dismantling often owe more to the tenacity of Native leaders who even to this day wish to remain within the church, than to the efforts of the dominant church members.